Research on the Multidimensional Frailty in Community-dwelling Older Adults - ZHAO Linlin, LUO Qi, HU Qinghua, CHEN Xiaolei, DU Juan, SHAO Shuang (Zhongguo quanke yixue)
The concept landscape of frailty has evolved from a single dimension which emphasising predominantly physical frailty into a multidimensional concept encompassing physical, psychological and social frailty. Conducting researches on multidimensional frailty armong community-dwelling older adults is an important way to address the current fragmentation of community-based elderly care services and enhance the comprehensive health of this population. In this paper, firstly, we review the evolution of the concept of multidimensional frailty; secondly, classify and describe the multidi. mensional frailty assessment tools that can be applied to community-dwelling older adults; thirdly, analysis the influencing factors of multidimensional frailty in community-dwelling older adults as well as the interactions between the dimensions of frailty, finally, assess the predictive value of multidimensional frailty in community-dwelling older adults in relation to health outcomes. Existing evidences suggest that the multidimensional frailty is found to be the result of a combination of physiological, psychological, and social factors, and that assessing multidimensional frailty in community-dwelling older adults can predict a variety of health outcomes such as disability, disease risk, and mortality, and that the different dimensions of frailty are correlated and interact with each others. However, there is no a standardized tool for evaluating multidimensional frailty in the community-dwelling older adults, and the underlying mechanisms of its occurrence and development have not been clarified. So, the follow-up studies could explore the developmental trajectory of multidimensional debility based on large prospective cohort studies, in order to provide a referable basis for the development of intervention strategies to reverse or delay the frail process in community-dwelling older adults.